Left temporal lobe epilepsy patients without Hippocampal Sclerosis: A DTI and VBM study. Issue 2 (2021) - Tsialios, Panagiotis; Karavasilis, Efstratios; Karanasiou, Irene; Bonakis, Anastasios; Velonakis, Georgios; Efstathopoulos, Efstathios
No abstract available